A Synthetic Tetramer of Galectin-1 and Galectin-3 Amplifies Pro-apoptotic Signaling by Integrating the Activity of Both Galectins - Farhadi, Shaheen A.; Fettis, Margaret M.; Liu, Renjie; Hudalla, Gregory A. (Frontiers in Chemistry, 2020)
Galectin-1 (G1) and galectin-3 (G3) are carbohydrate-binding proteins that can signal apoptosis in T cells. We recently reported that a synthetic tetramer with two G1 and two G3 domains (“G1/G3 Zipper”) induces Jurkat T cell death more potently than G1. The pro-apoptotic signaling pathway of G1/G3 Zipper was not elucidated, but we hypothesized based on prior work that the G1 domains acted as the signaling units, while the G3 domains served as anchors that increase glycan-binding affinity. To test this, here we studied the involvement of different cell membrane glycoproteins and intracellular mediators in pro-apoptotic signaling via G1/G3 Zipper, G1, and G3. G1/G3 Zipper induced Jurkat T cell death more potently than G1 and G3 alone or in combination. G1/G3 Zipper, G1, and G3 increased caspase-8 activity, yet only G1 and G3 depended on it to induce cell death. G3 increased caspase-3 activity more than G1/G3 Zipper and G1, while all three galectin variants required it to induce cell death. JNK activation had similar roles downstream of G1/G3 Zipper, G1, and G3, whereas ERK had differing roles. CD45 was essential for G1 activity, and was involved in signaling via G1/G3 Zipper and G3. CD7 inhibited G1/G3 Zipper activity at low galectin concentrations but not at high galectin concentrations. In contrast, CD7 was necessary for G1 and G3 signaling at low galectin concentration but antagonistic at high galectin concentrations. Collectively, these observations suggest that G1/G3 Zipper amplifies pro-apoptotic signaling through the integrated activity of both the G1 and G3 domains.